2007
DOI: 10.1021/bc0603788
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Evaluation of 64Cu-Labeled DOTA−Linker−Bombesin(7−14) Analogues Containing Different Amino Acid Linker Moieties

Abstract: The gastrin-releasing peptide receptor (GRPR) is overexpressed on a variety of tumor types and has been targeted with radiolabeled peptides for detection and therapy of these cancers. Analogues of the 14 amino acid bombesin (BN) peptide have been radiolabeled with both gamma- and positron-emitting radionuclides for detection of GRPR-expressing tumors. We have previously evaluated BN analogues radiolabeled with the positron-emitter, copper-64 (64Cu), that contained various aliphatic linkers placed between the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 27 publications
6
80
2
3
Order By: Relevance
“…The specificities of uptake for the tumor and the pancreas were 82% and 96%, respectively. 64 Cu-DOTA-bombesin peptides exhibited tumor uptake and good imaging characteristics (30). Our laboratories have focused on labeling peptides for PET of both breast cancer and prostate cancer with 18 F because this nuclide has ideal characteristics for peptide receptor imaging studies.…”
Section: In Vivo Characterizationmentioning
confidence: 99%
“…The specificities of uptake for the tumor and the pancreas were 82% and 96%, respectively. 64 Cu-DOTA-bombesin peptides exhibited tumor uptake and good imaging characteristics (30). Our laboratories have focused on labeling peptides for PET of both breast cancer and prostate cancer with 18 F because this nuclide has ideal characteristics for peptide receptor imaging studies.…”
Section: In Vivo Characterizationmentioning
confidence: 99%
“…[28][29][30] Many studies demonstrate that the BN(7-14) fragment modified on its N-terminus with radiometal complexes, for diagnostic or therapeutic nuclear medicine applications, preserves its affinity for these receptors. [31][32][33] In-vitro and in-vivo experiments, carried out on radiolabeled liposomes containing the BN (7)(8)(9)(10)(11)(12)(13)(14) peptide fragment, demonstrate that the peptide, exposed on the liposome surface, maintains the capability to selectively target aggregates to GRPR-expressing xenografts. 27 This paper describes new BN-conjugated nanosystems for theranostic purposes with improved properties, both in the synthesis and formulation aspects and for their in-vitro and in-vivo behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in the tumor uptake and pharmacokinetics of 64 Cu-labeled cyclic RGD peptides using Gly-Gly-Gly (GGG) and polyethyleneglycol 4 (PEG4) linkers has been reported (29). Other studies indicated that prostate tumor uptake of 64 Cu-labeled DOTA-bombesin peptide with a GGG-linker was higher than that with a GSG-linker, although kidney uptake was higher (30). Future work will focus on evaluating and optimizing the pharmacokinetic profile of 64 Cu-NO2A-TFpep using more than 1 linker group based on hydrocarbons, PEG, or amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…MDA-MB-435 and 184A1 cells grown in culture flasks were trypsinized, released, and washed once in cell-binding medium (RPMI 1640 with 25 mM N-(2-hydroxyethyl)piperazine-N9-(2-ethanesulfonic acid), pH 7.4, 0.2% bovine serum albumin [BSA], and 3 mM 1,10-phenanthroline). Cells (2 · 10 5 cells per tube) were transferred to microcentrifuge tubes containing 0.3 mL of cell-binding medium and were incubated at 37°C for different times (10,20,30,40, and 60 min) with 1 · 10 5 counts per min (cpm) of radiolabeled and scrambled peptide. After incubation, medium was removed and the cells were rinsed with ice-cold 0.01 M phosphate-buffered saline (PBS), pH 7.4, and 0.2% BSA, and then centrifuged.…”
Section: Cell-binding Studiesmentioning
confidence: 99%